MENINGKATKAN KEINGINTAHUAN ANAK MELALUI KEGIATAN BERCERITA PADA KELOMPOK A DI TK TAMANSARI SURABAYA - Gusmaniarti Gusmaniarti; Andini Widya Agustina; Aulia Navisa Hidayati Vizaa; Anisa Karim; Indah Putri Syaqinah (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
The background in this study is the fact that in Tamansari Surabaya Kindergarten, children's curiosity has not been well developed. For this reason, the purpose of this study is to increase understanding of early childhood through storytelling activities in group A at TK Tamansari Surabaya. Researchers use this type of research in the form of classroom action research. The approach applied is a case study approach with qualitative methods. The location of this research was at Tamansari Surabaya Kindergarten which was conducted for 2 days on 8-9 December 2022 with 20 students as kindergarten students in group A as research subjects. The data collection technique is observation and documentation. The data analysis technique used is descriptive comparative statistical techniques. The results of the research and discussion are based on cycle 1 and cycle 2. At cycle 1 to 1 meetings, storytelling activities are carried out using storybook media. Of which there are only 5 children (25%) who focus on learning. Meanwhile, the success rate must reach 80% of 20 children. Then, the researcher reflected by holding meeting 2 in cycle 1. Meeting 2 revealed storytelling activities using media images that had not succeeded in reaching the target. Because the number of children who focused on listening to stories was only 8 children (40%). Then, the researcher reflected again by holding cycle 2. In cycle 2, storytelling activities used hand puppet media. With the media of hand puppets, students are more enthusiastic in listening to stories. Cycle 2 described that the number of children who focused on learning increased to 18 children (90%). So it can be concluded that this research was successful. Because storytelling activities can increase children's curiosity at Tamansari Surabaya Kindergarten. And the media that is effectively used in storytelling activities is the hand puppet media.